2021
DOI: 10.3390/molecules26041004
|View full text |Cite
|
Sign up to set email alerts
|

Tannic Acid-Stabilized Silver Nanoparticles Used in Biomedical Application as an Effective Antimelioidosis and Prolonged Efflux Pump Inhibitor against Melioidosis Causative Pathogen

Abstract: Burkholderia pseudomallei is the causative pathogen of melioidosis and this bacterium is resistant to several antibiotics. Silver nanoparticles (AgNPs) are an interesting agent to develop to solve this bacterial resistance. Here, we characterize and assess the antimelioidosis activity of AgNPs against these pathogenic bacteria. AgNPs were characterized and displayed a maximum absorption band at 420 nm with a spherical shape, being well-monodispersed and having high stability in solution. The average size of Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 71 publications
(104 reference statements)
2
3
0
Order By: Relevance
“…The results obtained for the rate of killing by the CAgNPs showed reductions in the populations of all the clinical bacterial isolates: E. coli strain MRE 600 (CP014197.1), Salmonella enteric subsp. Enteric serovar typhi PMO 16/13 (CP12091.1), K. pneumoniae strain HZW25 (CP025211.1) and P. fluorescens strain 2P24 (CP025542.1) between the periods of 1-7 h. These results were similar to the ones obtained in the studies of Betts et al (2018); Smirnova and Oktyabrsky (2018); Srichaiyapol et al (2021), in which there was a reduction in the population of the bacteria as the time of exposure increased. The value of 0.00log 10 cfu/ml was obtained at the sixth and seventh hours when E. coli strain MRE 600 (CP014197.1) was exposed to the CAgNPs, possibly showing the most significant bactericidal effect on E. coli strain MRE 600 (CP014197.1) followed by Salmonella enteric subsp.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results obtained for the rate of killing by the CAgNPs showed reductions in the populations of all the clinical bacterial isolates: E. coli strain MRE 600 (CP014197.1), Salmonella enteric subsp. Enteric serovar typhi PMO 16/13 (CP12091.1), K. pneumoniae strain HZW25 (CP025211.1) and P. fluorescens strain 2P24 (CP025542.1) between the periods of 1-7 h. These results were similar to the ones obtained in the studies of Betts et al (2018); Smirnova and Oktyabrsky (2018); Srichaiyapol et al (2021), in which there was a reduction in the population of the bacteria as the time of exposure increased. The value of 0.00log 10 cfu/ml was obtained at the sixth and seventh hours when E. coli strain MRE 600 (CP014197.1) was exposed to the CAgNPs, possibly showing the most significant bactericidal effect on E. coli strain MRE 600 (CP014197.1) followed by Salmonella enteric subsp.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the TEM result (Figure 3) revealed that the CAgNPs are spherical in shapes that facilitate the delivery of drugs to the target sites, as reported in the studies of Govindaraju et al (2010); Saeed et al (2020). The presence of silver as revealed by the EDS spectrum (Figure 3) in the characterized CAgNPs is similar to the results obtained by Samuggam et al (2021); Srichaiyapol et al (2021), in which silver was also present.…”
Section: Discussionsupporting
confidence: 81%
“…The first mention of AgNPs as EPIs we found in a 2018 publication, in which obtained results only provided circumstantial (not direct) evidence indicative of AgNPs functioning as EPIs [12]. For the last three years, the articles published results of in vitro experiments showing that AgNPs can decrease the efflux pump gene expression, reduce expression of functional efflux pump proteins, inhibit activity of P-glycoprotein (Pgp, the drug transporters that determine the uptake and efflux of drugs), or change efflux pump activity [12][13][14][15][16][17][18][19][20][21][22]. These results were obtained with application of AgNPs alone or in combination with antibiotics or other drugs, to which microorganisms or cells had already developed resistance.…”
Section: Introductionmentioning
confidence: 99%
“…These results were obtained with application of AgNPs alone or in combination with antibiotics or other drugs, to which microorganisms or cells had already developed resistance. These publications include influence of AgNPs on the efflux effect of P. aeruginosa [13][14][15], Escherichia coli [17][18][19], A. baumannii [14][15][16], K. pneumonia [20,21], Burkholderia pseudomallei [22], E. cloacae [12]. Moreover, the influence of AgNPs on the efflux effect was studied on Bifidobacterium bifidum probiotic, the drug-resistant cancer MCF-7/KCR cell line [23], and planktonic cells and biofilms [24].…”
Section: Introductionmentioning
confidence: 99%
“…3C). 120 In summary, bacteria have evolved various resistance mechanisms against antibiotics. How to rebuild the sensitivity of drug-resistant bacteria to the present antibiotics or nd alternatives to synthetic antibiotics to combat bacteria is a big challenge to human beings.…”
Section: Degradation Of Antibioticsmentioning
confidence: 99%